A study on the correlation between precipitation with temperature, relative humidity and evaporation by using R² multiple regression analysis - Hisyammudin, bin Maseri (Universiti Malaysia Sarawak (UNIMAS), 2014)
Precipitation is one of the parameter in hydrological cycle and this process begins when heat from the sun evaporates water from Earth's surface. However, evaporation is depends both on its temperature and on the concentration of humidity. The objective of this study is to identify the highest correlation factor R2 between precipitation with combination temperature, evaporation and humidity in general without considering monsoon and by taking into account monsoon aspect (North-East and South-West monsoon) at Kuching International Airport, Sibu Airport, Bintulu Airport and Miri Airport station. Simple regression analysis and multiple regression analysis were adopted in this research to determine the correlation factor R2 value where precipitation as a dependent variable while temperature, humidity and evaporation as an independent variable. There were seven relationships tested in this study: (i) P-THE, (ii) P-TH, (iii) P-TE, (iv) P-HE, (v) P-T, (vi) P-H, and (vii) P-E. The outcome from relationship between dependent variable of precipitation with combination dependent variable (P-THE) from the multiple regressions analysis contributed the highest R2 value: (i) without considering monsoon (ii) considering monsoon for all stations.